2012
DOI: 10.3844/ajidsp.2012.168.174
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram of Bacteria Isolated From Automated Teller Machines Within Abakaliki Metropolis

Abstract: The Automated Teller Machine (ATMs) is likely to be contaminated with various microorganisms due to their vast dermal contact by multiple users. The metallic keypads of ATMs were examined to investigate their potentials as source of bacterial contamination and also the antibiogram of the isolated organisms. The study lasted from August, 2012 to October, 2012 involving several procedures like culturing, identifying the organisms using biochemical tests and Kirby Bauer disc diffusion method for antibiotic sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 18 publications
9
21
0
Order By: Relevance
“…This discrepancy might be due to different geographical locations. The results of the present study are in accordance with those of Abban et al [ 9 ] and Okoro Nworie et al [ 30 ], who reported the presence of Staphylococcus spp., E. coli , and Klebsiella spp. on the keyboards of ATMs.…”
Section: Discussionsupporting
confidence: 93%
“…This discrepancy might be due to different geographical locations. The results of the present study are in accordance with those of Abban et al [ 9 ] and Okoro Nworie et al [ 30 ], who reported the presence of Staphylococcus spp., E. coli , and Klebsiella spp. on the keyboards of ATMs.…”
Section: Discussionsupporting
confidence: 93%
“…The ATM keypad can be considered a highly trafficked surface that routinely comes into contact with human inhabitants, similarly to railings, seats, and turnstiles in urban transit systems (28, 29). Several culture-based studies of ATMs around the world have previously been carried out (3133), but no study to date has yet applied high-throughput sequencing methods to deeply characterize all taxa which may be present on ATM keypads. In the present study, we sampled ATM keypads across eight neighborhoods in three NYC boroughs, where US Census data indicated the presence of demographically distinct populations of local residents (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all the bacteria were sensitive to the commercially available disinfectants suggesting that the use of these disinfectants by contaminated individuals in the form of hand cleaning may reduce the spread. Also, regular disinfection of the ATMs with the commercially available disinfectants will reduce the spread of the bacteria among users of the ATM [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Though, microorganisms that could be pathogenic were found on some of the ATMs, some studies showed that they are unlikely to cause infections except in immunocompromised individuals [1].…”
Section: Resultsmentioning
confidence: 99%